PENCAPAIAN KEBUN RAYA INDONESIA DALAM TARGET 8 GLOBAL STRATEGY FOR PLANT CONSERVATION (GSPC) - Purnomo, Danang Wahyu; Hendrian, R.; Witono, Joko Ridho; Kusuma, Yayan Wahyu Candra; Risna, Rosniati Apriani; Siregar, Mustaid (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2010)
Target 8 of the Global Strategy for Plant Conservation (GSPC) has a very close link to the works of botanic gardens. It highlights the importance of ex situ collections of threatened plants and their recovery programme. The aim of this paper was to present the Indonesian Botanic Gardens achievements in implementing Target 8 of the GSPC. It is shown that to date 21.5% of Indonesian threatened plants have already been collected ex situ in Indonesian Botanic Gardens. The reintroduction programme was also initiated. In its 14th meeting this year, SBSTTA recommended proposal for an updated GSPC (for 2011-2020), in which the Target 8 was changed to